Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Keuangan Melalui Perilaku Konsumtif Sebagai Variabel Intervening: Indonesia - Pingky Karamoy; Risal Rinofah; Ratih Kusumawardhani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study was to determine how financial literacy and lifestyle on financial behaviour through consumptive behaviour as an intervening variable in students of Sarjanawiyata Tamansiswa University Yogyakarta. The research population consisted of 100 respondents. Random sampling is the sampling method. collected through questionnaires, and processed through classical assumption tests, multiple linear regression analysis, and sobel tests. The classical assumption test includes normality test, muticolonierity test, and heteroscedasticity test. The results of this study if H1 Financial literacy has a significant positive effect on consumptive behaviour. H2 Lifestyle has a significant positive effect on Consumptive Behaviour. H3 Financial Literacy has a significant positive effect on Financial Behaviour. H4 Lifestyle has a significant positive effect on Financial Behaviour. H5 Consumptive Behaviour has a significant positive effect on Financial Behaviour. Consumptive behaviour variables can influence financial literacy and lifestyle on financial behaviour. Future research can add more variables to measure financial and consumptive behaviour.